2018
DOI: 10.1093/jas/sky458
|View full text |Cite
|
Sign up to set email alerts
|

The effect of orexin B on steroidogenic acute regulatory protein, P450 side-chain cleavage enzyme, and 3β-hydroxysteroid dehydrogenase gene expression, and progesterone and androstenedione secretion by the porcine uterus during early pregnancy and the estrous cycle1

Abstract: The aim of this study was to investigate the effect of orexin B (OXB) on progesterone (P 4) and androstenedione (A 4) secretion by porcine endometrial and myometrial tissue explants and on the expression of key steroidogenic proteins and enzymes involved in steroid production. The hormones secretion and the expression of steroidogenic acute regulatory protein (StAR), P450 side-chain cleavage enzyme (CYP11A1), and 3β-hydroxysteroid dehydrogenase (HSD3B1) were analyzed on days 10 to 11, 12 to 13, 15 to 16, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The other prominent steroidogenic enzyme present in the endometrium was HSD3B2. Previously known as HSD3B1, this enzyme has been reported in the equine chorioallantois [32] and testis [54], as well as early pregnant porcine endometrium[55], but hasn’t previously been studied in the equine endometrium. In contrast, INHBA has been previously reported to be endometrium-specific [56], although these data suggest that it is also expressed at a lower, yet still significant, level in the chorioallantois (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The other prominent steroidogenic enzyme present in the endometrium was HSD3B2. Previously known as HSD3B1, this enzyme has been reported in the equine chorioallantois [32] and testis [54], as well as early pregnant porcine endometrium[55], but hasn’t previously been studied in the equine endometrium. In contrast, INHBA has been previously reported to be endometrium-specific [56], although these data suggest that it is also expressed at a lower, yet still significant, level in the chorioallantois (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, the residual data obtained in our previous studies seem to confirm that OXB participates in the expression of uterine genes and macromolecules biosynthesis processes. Our previous research revealed that OXB exerted a dose‐dependent influence on the expression of genes encoding enzymes that are crucial for steroidogenesis, as well as the production and secretion of steroids such as testosterone, progesterone and oestradiol in the porcine uterus during early gestation (Kaminski et al., 2018; Kisielewska et al., 2019). An analysis of the interactions between DEG also confirmed that OXB affects the genes linked with lipid transport, steroid metabolism, hormone binding and regulation of hormone levels, which seems to confirm that OXB modulates endometrial gene expression and the biosynthesis of macromolecules, including key steroid enzymes and factors.…”
Section: Discussionmentioning
confidence: 99%
“…The above suggests that orexins' effects could be modulated by specific local factors in different phases of the oestrous cycle or pregnancy (Nitkiewicz et al., 2012; Smolinska et al., 2015). Our previous studies demonstrated that OXB modulates the expression of genes encoding crucial steroidogenic enzymes and proteins, including the cytochrome P450 side‐chain cleavage enzyme ( CYP11A1 ), 3β‐hydroxysteroid dehydrogenase ( HSD3B1 ), steroidogenic acute regulatory protein ( StAR ), cytochrome P450 aromatase ( CYP19A3 ) and cytochrome P450c17 ( CYP17A1 ), and influences the secretion of progesterone, androstenedione, testosterone, oestrone and oestradiol by porcine uterine tissues during early gestation and in the luteal phase of the oestrous cycle (Kaminski et al., 2018; Kisielewska et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the role of OXB and OX2R in the regulation of reproductive activity has been poorly investigated. Kaminski et al [ 18 ] and Kisielewska et al [ 19 ] documented an involvement of OXB in the regulation of steroidogenesis by the porcine uterus during the luteal phase and early pregnancy. As for the gonads, Liguori et al [ 20 ] provided the first evidence of OXB and OXR2 localization within the rat epididymis.…”
Section: Introductionmentioning
confidence: 99%